Pei Xiu (791–864) and Lay Buddhism in Tang Chan - Wu, Jiang (Journal of Chan Buddhism, 2020)
Pei Xiu 裴休 (791–864) was a literati follower of Buddhist teachers, among whom the two most eminent were Zongmi 宗密 (780–841) and Huangbo Xiyun 黃檗希運 (?–850). These two teachers had notably different spiritual orientations: one was the synthesizer of Chan and Huayan teachings, the other a member of the more radical Hongzhou 洪州 school. Rather than passively patronizing Buddhist teachers, Pei Xiu served as an active agent of his own religiosity and influenced Buddhist communities broadly. Through examining Pei Xiu’s Quanfa putixin wen 勸發菩提心文 [Essay Exhorting the Generation of Bodhicitta], Chuanxin fayao 傳心法要 [Essentials of The Transmission of Mind], which he prefaced and edited, and his various prefaces and epitaphs written for Zongmi and other monks, this study scrutinizes the transformation of early Chinese Chan communities before they were reimagined as ‘mature’ and ‘classical’ in later times.